Cention-N: a direct and innovative restorative option for the posterior sector - Midian Clara Castillo Pedraza; Hans Kepler Becerra López; Jorge Homero Wilches Visbal (Revista Cubana de Medicina Militar)
Introduction: Dental industry is constantly evolving regarding the realization of dental materials that improve the quality of life. However, due to the large number of these, it is essential to perform intercomparisons of biomechanical properties that define those with the best performance. Objective: To identify the advantages and disadvantages of Cention-N restorative material with respect to composite resin, glass ionomer and amalgam. Methods: A bibliographic search was made in the PubMed, Scielo, Semantic Scholar, ScienceDirect, Medigraphyc and Redalyc databases. The following keywords were used: Cention-N, restorative material, amalgam, composite resin, the glass ionomer; combined with Boolean AND and OR operators. Original and review articles, among other documents, were chosen to examine 4 characteristics: microfiltration, hardness, surface roughness and shear resistance. 50% of the articles are from the last 5 years. Results: A total of 13 articles, 1 webpage and 1 book, were found according to the selection filters and research objective. The Cention-N, with respect to the other materials considered, presented a lower microfiltration score (0,28 ± 0,18); higher hardness (77 N / mm2); lower roughness (442,98 ± 62,45 nm) and higher shear strength (14,38 ± 3,88 MPa). However, it remains to evaluate its mechanical properties before abrasive procedures such as teeth whitening and at high loads such as bruxism. Conclusion: Cention-N is a promising option as a posterior sector restorative material as it shows less microfiltration and roughness; as well as greater resistance to shear and hardness, compared to other restorative materials studied.